Exposure to electrocution by automotive ignition system in the work environment of car service employees - Bernard Fryśkowski; Dorota Świątek-Fryśkowska (Nofer Institute of Occupational Medicine, 2014)
Automotive ignition system diagnostic procedures involve a specific kind of action due to the presence of high voltage pulses rated of roughly several dozen kilovolts. Therefore, the repairers employed at car service coming into direct contact with electrical equipment of ignition systems are exposed to risk of electric shock. Typically, the electric discharge energy of automotive ignition systems is not high enough to cause fibrillation due to the electric effect on the heart. Nevertheless, there are drivers and car service employees who use electronic cardiac pacemakers susceptible to high voltage pulses. The influence of high-voltage ignition systems on the human body, especially in case of electric injury, has not been comprehensively elucidated. Therefore, relatively few scientific papers address this problem. The aim of this paper is to consider the electrical injury danger from automotive ignition systems, especially in people suffering from cardiac diseases. Some examples of the methods to reduce electric shock probability during diagnostic procedures of spark-ignition combustion engines are presented and discussed. Med Pr 2014;65(3):419-427